Atrakcyjność inwestycyjna polskich województw - Stawicka, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main aim of this article is analyze the attractiveness of investment in Polish provinces on the basis of the audit conducted among foreign investors relating to investment factors. According to businessmen, the most important factors determining the level of investment are: the size of market, absorptiveness of market, economic growth, accessibility of cheap labour, existing as well as planned infrastructure, functioning of Special Economic Zones. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 320-334